PERBANDINGAN DAMPAK LINGKUNGAN PRODUKSI SKALA LABORATORIUM CAMPURAN ASPAL MODIFIKASI POLIMER DENGAN METODE CAMPURAN BASAH DAN KERING MENGGUNAKAN LIFE CYCLE ASSESSMENT (LCA) - Daniel, Christian Gerald; Rifqon, M.; M. Firdaus, Fadhil; A. Canny, Khairina (Direktorat Bina Teknik Jalan dan Jembatan, 2023)
This study evaluates the environmental impact of polymer-modified bituminous mix production through wet-mixed polymer-modified bitumen (PMB) and direct, dry mixing technique using the Life Cycle Assessment (LCA) method based on emission monitoring in the lab for 5 samples per each type of mix. Ethylene-Vinyl Acetate (EVA) of 5% and 6% bitumen weight was incorporated for the dry mix. The scope of this study was from raw material acquisition to lab-scale production. Emission monitoring from the sample production stage in the lab showed that producing PMB-based samples increased CO2 concentration by 21.78 – 38.3%, Volatile Organic Compound by 16.69 – 28.93%, as well as formaldehyde and particulate matter by 14.6 – 20.17% and 7 – 37%, all were due to a higher heating temperature. LCA outcomes showed that the Global Warming Potential impact category of 5 PMB sample production was 2.8kg CO2-eq, increasing by 1.1 – 4.1%. The Freshwater Aquatic Ecotoxicity Potential of 5 PMB samples production was 0.32 kg 1.4-DB eq, 9.15 – 12.33% higher than the EVA-modified specimens, and both Human Toxicity and Photochemical Oxidation increased by 14.35 – 25% to 167 kg 1.4-DB eq and 0.00081 kg C2H4 eq. The Marshall Quotient and Stability of the EVA-Modified mix were 67.7% higher and 14% lower than the PMB-based specimens with similar volumetric properties, indicating an eco-friendlier solution from the dry-blended polymer-modified asphaltic mixtures approach with similar properties.